Pengembangan Instrumen Asesmen Diagnostik Kognitif Berbantuan Quizizz pada Materi Sistem Pernapasan Manusia - Shaleha, Musrifatus; Hakim, Miftahul; Hasbiyati, Haning (FKIP Universitas Islam Jember, 2024)
Implementation of learning according to the independent curriculum consists of three stages, namely diagnostic assessment, planning, and learning. The aim of this research is (1) to produce a valid and practical quizizz-assisted cognitive diagnostic assessment instrument on the human respiratory system, and (2) to help teachers carry out diagnostic assessments effectively. The results show that the validity test of the cognitive diagnostic assessment instrument obtained a percentage result of 84% (very feasible) by material experts and 80% (adequate) by evaluation experts. From this, it can be concluded that the quizizz-assisted cognitive diagnostic assessment instrument on the human respiratory system material can be used without any revisions. In the practicality test of teacher and student responses, the percentage results were 76% of student responses and 80% of teacher responses with good interpretation.